Internationalization strategy of reliance to Brazil - Girão, João Pedro Fonseca (2015)
This Work Project was focused, firstly, in an internal analysis to assess the possible competitive advantage sources of the firm and to identify the key weakness that the firm should improve before advancing with the internationalization strategy. Completed the analysis was possible to verify that the source of sustainable competitive advantage of Relance is the use of specific raw materials and that its biggest weaknesses are the lack of capacity and the excessive dependence on key employees. Overall, it was possible to conclude that the firm is in position of competing in the international markets. Secondly, due to its crucial importance, the country selection was made with a deep objective analysis, resulting with the selection of Brazil as the country with the highest market potential. Regarding the strategy to actually enter in Brazil’s market, after the study of 12 modes of entry it was possible to conclude that there is no ideal mode. However, the study performed allowed to undertake the conclusion that in order to obtain long-term optimization on the process, the adaptation, to the firm´s situation, of the Uppsala model progressive stages is the ideal. At the course of this Work Project it was inferred that the critical success factors are the choice of the distributor and the promotion of Relance as a premium brand.